Learning Cycle 5E Model and Junior High School Students’ Scientific Literacy: Model Siklus Pembelajaran 5E dan Literasi Ilmiah Siswa Sekolah Menengah Pertama - Larasati, Faninda; Shofiyah, Noly (Indonesian Journal of Education Methods Development, 2025)
General Background: Scientific literacy is a crucial 21st-century skill that enables students to apply scientific knowledge in solving real-life problems. Specific Background: In Indonesia, the results of PISA consistently show low levels of scientific literacy among students, highlighting the need for effective instructional models. Knowledge Gap: Previous studies have explored the Learning Cycle 5E model but rarely examined its role in addressing scientific literacy using the Pan-Canadian Assessment Program (PCAP) indicators. Aim: This study aimed to investigate the Learning Cycle 5E model in improving scientific literacy among junior high school students. Results: Using a quantitative pre-experimental design with a one-group pretest-posttest, findings revealed an N-gain of 0.6 (moderate category) and no significant differences across classes based on ANOVA (p = 0.126). Analysis of indicators showed improvements with scientific inquiry (70%, good), problem-solving (56%, fairly good), and scientific reasoning (43%, fairly good). Novelty: The study highlights the integration of PCAP indicators into the Learning Cycle 5E framework, providing a structured evaluation of scientific literacy beyond content mastery. Implications: These findings suggest that the 5E model supports active and inquiry-based learning, which can be adapted by teachers to foster better scientific literacy outcomes in junior high schools. Highlights : Structured evaluation of scientific literacy using PCAP indicators Improvement in scientific inquiry, problem solving, and reasoning Practical guidance for teachers in junior high school science Keywords: Learning Cycle 5E, Scientific Literacy, PCAP Indicators, Junior High School, Science Education